Influence of Celebrity Endorsement, Price Perception, and Product Quality on Purchase Decision of Ventela Products - Tiara Khurnia Illahi; Misti Hariasih; Dewi Komala Sari (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the influence of celebrity endorsement, price perception, and product quality on purchasing decisions of Ventela brand shoes. Methodology: This research employs a quantitative approach using a survey method. The population consists of consumers who have purchased and used Ventela products. A non-probability sampling technique with a purposive sampling approach was applied, involving 100 respondents. Data were collected through a Google Form–based questionnaire using a Likert scale and analyzed using Smart PLS software. Results: The results indicate that celebrity endorsement, price perception, and product quality have a positive and significant effect on purchasing decisions. Findings: Among the examined variables, product quality has the most dominant influence on consumers’ purchasing decisions. Novelty: This study integrates celebrity endorsement, price perception, and product quality simultaneously to explain purchasing decisions in the context of local footwear brands. Originality: The research provides empirical evidence on consumer purchasing behavior toward Ventela shoes using a PLS-based quantitative approach. Conclusion: Celebrity endorsement, price perception, and product quality significantly influence purchasing decisions, with product quality being the strongest determinant. Type of Paper: Research Article